The Clinical Effectiveness of Post-Brushing Rinsing in Reducing Plaque and Gingivitis: A Systematic Review - Prasad, Monika (J Clin Diagn Res, 2016)
INTRODUCTION: Dental plaque is the major etiological factor associated with the development of gingivitis. Hence, maintenance of oral hygiene is very essential. AIM: To systematically review the literature on the effects of a post toothbrushing rinsing on plaque and parameters of gingival inflammation. MATERIALS AND METHODS: A literature review was performed in PubMed Central and Cochrane library, embase, google scholar were searched up to February 2015 to identify appropriate studies. The primary outcome measure was plaque and gingival inflammation reduction. RESULTS: Out of the total 56 titles appeared, 08articles fulfilled the criteria and were selected for the review. One article which was hand searched and one article which was through e-mail was included. A statistically significant reduction in overall plaque and gingivitis was noted when different mouth rinses were compared to the control (p<0.05). It was seen that chlorhexidine is the best antiplaque and antigingivitis agent but due to its side effects after continuous use, was not indicated for long term use. Probiotic was superior to chlorhexidine in terms of reduction of gingival inflammation. CONCLUSION: There are relatively few studies evaluating the association between post toothbrushing rinsing and gingivitis. A clear effect was observed, indicating that different mouthrinses (chlorhexidine, probiotic, herbal, essential oil mouthrinse) when used as an adjunct to mechanical means of oral hygiene, provides an additional benefit with regard to plaque and gingivitis reduction as compared to a placebo or control.